Identification of the Real Hub Gene and Construction of a Novel Prognostic Signature for Pancreatic Adenocarcinoma Based on the Weighted Gene Co-expression Network Analysis and Least Absolute Shrinkage and Selection Operator Algorithms - Yuan, Qihang; Ren, Jie; Wang, Zhizhou; Ji, Li; Deng, Dawei; Shang, Dong (Frontiers in Genetics, 2021)
Background: Pancreatic adenocarcinoma (PAAD) carries a very bad prognosis, whose pathophysiologic mechanism remains to be studied. Thus, we aim to identify real hub genes for better exploring the pathophysiology of PAAD and construct a prognostic panel for better predicting the prognosis of PAAD using WGCNA and LASSO algorithms. Methods: Weighted gene co-expression network analysis (WGCNA) identified the modules most closely related to stage and grade of PAAD based on Gene Expression Omnibus. The module genes that were significantly associated with PAAD progression and prognosis were considered as the real hub genes. All the genes in the most significant module were selected for construction and validation of a multigene prognostic signature based on LASSO-Cox regression analysis in The Cancer Genome Atlas, and International Cancer Genome Consortium databases, respectively. Results: The brown module identified by WGCNA was most closely associated with clinical characteristics of PAAD. Scaffolds attachment factor B (SAFB) was detected to be significantly associated with progression and prognosis of PAAD and to be identified as the real hub gene of PAAD. Compared to normal pancreas tissues, both transcriptional and translational levels of SAFB were significantly lower in PAAD tissues. SAFB could be served as a novel independent prognostic indicator of PAAD. SAFB might improve prognoses of PAAD via increasing CD4+T cell inflitration. In addition, a novel multigene independent prognostic signature consisting of SAFB, SP1, and SERTAD3 was identified and verified. A prognostic nomogram based on a combination of independent prognostic variables was developed and was also validated by calibration curves. Potential mechanisms of different prognoses between high- and low-risk subgroups were investigated by functional enrichment analysis, GSEA, and ssGSEA. Conclusions: In summary, SAFB was identified as the real hub gene of PAAD. A novel mutligene independent prognostic signature was successfully identified and validated for better predicting the prognosis of PAAD.